Employing an in-silico approach in the evaluation of Aloe vera metabolites as inhibitors of Omicron RBD and the ROS-dependent cellular signaling processes - Billy Johnson Kepel, Marko Jeremia Kalalo, Trina Ekawati Tallei, Fatimawali (Journal of Applied Pharmaceutical Science, 2023)
The pathogenesis of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is related to increased reactive oxygen species (ROS) formation. This increasing ROS formation can mediate ROS-dependent cellular signaling processes inducing cytokines and inflammations that worsen the disease. The severity of coronavirus disease 2019 (COVID-19) can progress due to the self-sustaining cycle of ROS release, inflammatory mediators, and cellular damage. For the treatment, Aloe vera is a promising plant that has the potential to be used. In this study, therefore, we identified the metabolite composition of A. vera peel and gel using liquid chromatography-mass spectrometry (LC-MS). The metabolites were molecularly docked to Omicron receptor-binding domain (RBD) and ROS-producing enzymes to obtain medicinal compounds to inhibit these targets. The LC-MS analysis revealed the peel and gel compositions are distinct, in which 13 metabolites are identified in the peel and 12 in the gel. Furthermore, these metabolites might be promising inhibitors against Omicron variant SARS-CoV-2 RBD and ROS-producing enzymes based on the docking scores and the number of bonds formed. Thus, A. vera is one promising candidate for COVID-19 treatment due to its potential to alter the RBD function of forming a complex with ACE2 and inhibit the ROS-dependent cellular signaling processes related to COVID-19 pathogenesis and disease severity progression.